PENGARUH KETERSEDIAAN PRODUK DAN HARGA PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI POLJAM MART - Kurnia Agnes; Dedi Handoko; Andel Hopi Candra (Journal of Applied Accounting And Business, 2026)
This study aims to determine the effect of product availability and product price on consumer purchasing decisions at Poljam Mart. This research employed a quantitative method with an associative approach. The sample consisted of 100 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS Versi 25. The results indicate that product availability and product price have a positive and significant effect on purchasing decisions, both partially and simultaneously. Product availability (t = 6.043) and product price (t = 2.896) showed significance values below 0.05. Simultaneously, both variables significantly influenced purchasing decisions (F = 81.476). The coefficient of determination (R²) of 0.627 indicates that 62.7% of purchasing decisions are explained by product availability and product price. It can be concluded that proper product availability and appropriate pricing play an important role in improving consumer purchasing decisions at Poljam Mart.